Penerapan Manajemen Kas Dalam Kaitannya Dengan Pengendalian Kas, Hutang dan Piutang Dengan Memanfaatkan Laporan Arus Kas - Budiman, Asteria Caterinah; Pamungkas, Bambang (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
Cash is a firm 's most Iiquid asset and has a decisive position in keeping the smooth operations of the company. The larger the cash, the more Iiquid the company be. But larger cash means also low cash turnover. Thus, a cash management is necessary to effectively and efficiently manage the firm 's Iiquid asset. This research is aimed at investigating how PDAM Tirta Pakuan implement its cash management and relate it With the control ofcash-in-flow and cash-out-flow by utilizing the firm 's the cash flow. The result shows that PDAM TPKB implements its cash management and cash budget in the beginning ofperiod based on previous year 's report. The predicted budgetfor cash outflow when contpared With its realization in 2009 tend to be unfavorablefor thefirm, however the deviation is contradictive in 2010. Keywords : cash management, cash flow